La necesidad de garantizar la seguridad de las personas que participan en los procesos electorales - Skeen Sánchez, Mariel (My University, 2021)
Okay, here is the abstract for that thesis: This thesis, "LA NECESIDAD DE GARANTIZAR LA SEGURIDAD DE LAS PERSONAS QUE PARTICIPAN EN LOS PROCESOS ELECTORALES" (The Need to Guarantee the Security of Persons Participating in Electoral Processes), analyzes the alarming rise in violence during Mexican electoral cycles, particularly the high rates of homicide against candidates observed in the 2017-2018 process, and its detrimental effects on democracy and the fundamental rights to vote and be voted for. It argues that electoral violence, while related to the country's general insecurity, has distinct characteristics often linked to the influence of de facto powers like organized crime seeking to control territory and political outcomes, especially at the local level. The study examines basic electoral concepts, historical antecedents including the Colosio and Torre Cantú cases, Mexico's current legal framework (identifying significant gaps in personal security guarantees for participants), and compares the situation with Colombia and Chile, also considering the Inter-American Human Rights System's mechanisms. Concluding that the State's current efforts are insufficient, undermining democratic legitimacy and citizen participation , the thesis proposes strengthening civic education, enhancing security strategies through better coordination and a focus on the entire electoral cycle, and significantly reforming the electoral law (LGIPE) to create robust, detailed, and universally applicable mechanisms for requesting and implementing effective personal security measures for all candidates and participants throughout the process.
CAPÍTULO I. PROBLEMÁTICA Y CONCEPTOS BÁSICOS -- CAPÍTULO II. ANTECEDENTES -- CAPÍTULO III. REGULACIÓN JURÍDICA ACTUAL -- CAPÍTULO IV. DERECHO COMPARADO -- CAPÍTULO V. ANÁLISIS DE CASOS EN MÉXICO
Keywords: Derecho - Tesis